Crítica aos Direitos Humanos desde América Latina: contribuição da ética da libertação de Enrique Dussel - Guimarães, Lua Marina Moreira (2018)
The present work reflects on the theoretical foundations of Human Rights. Considering the famous contradiction between the status of Human Rights as the ethical center of legal systems in modern societies; and considering the selective lack of concrete effects especially in the peripheral nations, the following problem was formulated: which philosophical fundaments can be found for Human Rights, capable of assuring them legality, truth and concreteness, in the Latin-American Philosophy of Liberation? This main problem relates to the notions of subject, human dignity and justice forged by the Modernity. Those concepts are deeply connected with the legal function in the capitalist mode of production, and with the coloniality of power and knowledge. The research is based first, on the analysis of theoretical movements which provided justification for Human Rights, on the terms of Modernity, and continues with the search for different and original fundaments within Philosophy of Liberation and their Marxist critic. On the first chapter, there is a critic on the illuminist tradition, concentrated on the main liberal theorists, and on the most developed expression of modern moral philosophy, Kant’s work. The second chapter is an exploration of Enrique Dussel’s Ethics of Liberation concepts. When the author is deconstructing the modern ethics, he absorbs Marxist categories for ethical analysis, and proposes a material ethics of life, which could be, with its fundaments on alterity, human corporality and historical subjectivity, the basis for a new project of Human Rights, critical and anti-colonialist. The third and last chapter is about Politics of Liberation, the most recent phase of Dussel’s theory. It could represent the moment of concrete realization of a Human Rights project critical and anti-colonialist, but some limits were found in his refusal of political repercussion to Marxist categories that he had incorporated in his ethics. Other limits are the concepts of Politics, State and Law that result, sometimes, in an abstract model of analogy with ethical principles.